2019
DOI: 10.1186/s41936-019-0107-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative bioefficacy of seed and root extracts of a medicinal plant, Withania somnifera when administered to prepupae of lepidopteran insects, Spodoptera litura (Lepidoptera: Noctuidae) and Pericallia ricini (Lepidoptera: Arctiidae)

Abstract: Background: The lepidopterans, Spodoptera litura and Pericallia ricini, are polyphagous pests of agricultural importance. The unscrupulous and non-judicious use of chemical pesticides for controlling the insect pests has resulted into severe environmental hazards, threatening non-target organisms and human health. Results: Administration of seed and root extracts of a medicinal plant, Ashwagandha (Withania somnifera) to prepupae of two economically important insect pests viz. S. litura and P. ricini resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…According to Ahmed et al (1981), insecticidal potentials and biological activity A. indica extract caused deformation of emerged adults in Musca domestica. Such kind of detrimental effect has also been observed by Gaur & Kumar (2019) in S. litura treated with medicinal plant, Ashwagandha (Withania somnifera).…”
Section: Resultsmentioning
confidence: 75%
“…According to Ahmed et al (1981), insecticidal potentials and biological activity A. indica extract caused deformation of emerged adults in Musca domestica. Such kind of detrimental effect has also been observed by Gaur & Kumar (2019) in S. litura treated with medicinal plant, Ashwagandha (Withania somnifera).…”
Section: Resultsmentioning
confidence: 75%
“…Nenotek et al (2022) reported that the methanol extract of A. Similarly, Root and seed extracts of Withania somnifera were tested against S. litura and Pericallia ricini at doses of 5, 10, 15, and 20 µg/ ml which revealed an abnormal pupae, delayed pupal-adult ecdysis, reduced pupation and adult emergence (Gaur et al, 2019). Shaalan et al (2005) reported that many botanicals have an effect on insect development, growth, and adult emergence.…”
Section: Resultsmentioning
confidence: 99%
“…The extract of various parts in W. somnifera has been reported as a potent insect growth regulator ( Gaur and Kumar, 2017 , 2018 ; Gaur and Kumar, 2019 ). The current study has focused on different effects of methanolic seed extract of this plant exerted on an important pest of mulberry.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also reported increased larval, pupal and adult duration after incorporation of root extract. Morphological and various growth disorders have been recorded in Spodoptra litura Fab (Lep: Noctuidae) (Gaur and Kumar, 2019).The prepupal treatment by root and seed extracts on S. litura and Peicalliaa ricini Fab (Lep: Arcttidae) showed that the seed extract exhibited mortality but not the root extract (Gaur and Kumar, 2020). Winter cherry extracts (aqueous suspension, ether and water) of roots, stems, leaves and fruits have been used against Callosobruchus chinensis L (Coleoptera: Chrysomelidae) adults where a 63.33% mortality have been observed using 10% ether extracts of its roots (Gupta and Srivastava, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation